Analisis Keterampilan Membaca Pemahaman Teks Dongeng Kelas ll di SDN Cigaling Kabupaten Tangerang - Aris Setiawan Adji; Nur Latifah; Sumiyani Sumiyani (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2026)
This research aims to explore the comprehension or silent reading skills of class II students at SDN Cigaling, Tangerang Regency. The study focuses on describing how students understand written texts when reading silently and how these skills are reflected during classroom learning activities. The approach used in this research is a qualitative descriptive method, with observation, interviews, and documentation employed as data collection techniques. The instruments used included interview guidelines for teachers and class II students, supported by classroom observation notes and relevant learning documents. The research sample consisted of 29 class II students at SDN Cigaling, Tangerang Regency. Based on the results of observations and interviews, it can be concluded that students’ reading comprehension or silent reading skills at SDN Cigaling, Tangerang Regency, are classified as good and are in accordance with various aspects of reading comprehension skills. Students were generally able to understand reading content, identify important information, and respond to questions related to the texts they read. These findings indicate that the learning approach implemented at the school supports the development of students’ reading skills effectively and contributes positively to improving their ability to read silently with understanding.